THE ROLE OF MAJELIS AKHYARUL WIDAD AS A MEDIUM FOR CULTIVATING LOCAL COMMUNITY MORALITY AT PONDOK ILMU BAITUL AKHYAR, KARANGLUHUR, KALIANGET, WONOSOBO - Ahmad Toha; sri Haryanto; Vava Imam Agus Faisal (Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2025)
In this era of rapid technological advancement, human life is compelled to keep pace, prompting diverse perspectives across society regarding these changes. Particular concern arises from negative impacts-such as unwise internet usage and a lack of information filtering-which can inadvertently lead to societal issues, including the erosion of morals, character, etiquette, and social values.The primary objective of this study is to describe and analyze the role of the Majelis Akhyarul Widad as a medium for fostering community morality at the Pondok Ilmu Baitul Akhyar in Karangluhur, Kalianget, Wonosobo. This study employs a descriptive qualitative approach utilizing observation, interviews, and documentation. Data analysis involves data collection, reduction, presentation, and drawing conclusions. The approach is grounded in the concept of taqwa (piety), emphasizing steadfastness (istiqamah), sincerity (ikhlas), attentive listening, deep internalization, and a genuine understanding of the recited texts among the congregation